TW37 enhances the pro-apoptosis and anti-migration ability of gefitinib in Non-Small Cell Lung Cancer - Chen, Xiaofan; Mao, Guangxian; Chen, Hua; Liu, Suyue; Wang, Sichao; Li, Xiaoqiang; Ye, Yiwang; Wu, Hao; Liu, Jixian (Cellular and Molecular Biology, 2018)
B cell leukemia-2 (Bcl-2) plays important roles in the development of tumor and drug resistance. The growth of tumor cells can be inhibited by downregulating the abnormal expression of Bcl-2 protein. TW37, an effective inhibitor of Bcl-2 protein, has now been widely studied in many tumors. In our study, it was found that TW37 exerted a significant effect on the proliferation, apoptosis and migration of Non-Small Cell Lung Cancer cells. Bcl-2 is also a key downstream factor of many signaling pathways such as Epidermal Growth Factor Receptor (EGFR). TW37 enhanced the inhibition of tumorigenesis by gefitinib, an EGFR-Tyrosine Kinase Inhibitor drug. Moreover, TW37 can promote apoptosis ability by inhibiting the phosphorylation level of EGFR protein in H1975 cells. Overall, TW37 enhances the pro-apoptosis and anti-migration ability of gefitinib in Non-Small Cell Lung Cancer.